Comparison of three different techniques for internal jugular vein cannulation under real time ultrasound guidance - Mahajan, Reena; Malhotra, Suchitra (International Journal of Clinical Trials, 2021)
Background: Ultrasound (USG) guided Internal jugular venous (IJV) cannulation is preferred than traditional approach due to increase in success rate, reduction in time taken and attempts of successful cannulation and less complications. The purpose of our study was to observe and compare three different real time 2-dimensional US-guided approaches and to determine which approach improves rate of successful cannulation, decreases complications along with shorter average time taken for the procedure. Primary outcomes of the study were venous access time, catheterization time and success rate. Secondary outcomes were number of patients requiring second attempt and complications observed. Methods: 120 adult patients were randomly divided into three groups according to real time US guided cannulation done with SAX-OP approach, LAX-IP approach and OAX-IP approach. Parameters like venous access time, catheterization time, number of patients requiring second attempt and complications were noted. Results: Venous access time was shortest in LAX group 21.84±3.67 seconds which was just significant statistically. Catheterization time was shortest in LAX group 241±123 seconds. Cannulation success rate was highest in LAX group 98% and was statistically significant. Patients requiring second attempt was least in LAX group 2.5%. Posterior IJV wall puncture was observed in 10% patients in SAX group and none in LAX and OAX group which was statistically significant. Conclusions: LAX-IP showed better performance in terms of higher cannulation success, lesser average venous access time and catheterization time and lesser complications. On toggling USG probe, both IJV and carotid artery can be differentiated and carotid puncture could be avoided. Hence LAX approach is safer and effective approach.